Neutrophil Lymphocyte Ratio, Platelet Lymphocyte Ratio and Mean Platelet Volume; which one is More Predictive in the Diagnosis of Pelvic Inflammatory Disease? - Kerem Doğa Seçkin; Mehmet Fatih Karslı; Burak Yücel; Burak Özköse; Doğukan Yıldırım; Berna Aslan Çetin; Halil Aslan (Medical Network, 2016)
OBJECTIVE: In the present study, we aimed to assess and compare the utility of complete blood count (CBC) parameters and C-reactive protein (CRP) in the diagnosis of pelvic inflammatory disease (PID). STUDY DESIGN: Sixty-six patients diagnosed with PID, and 200 healthy control subjects were included in this case-control study. The groups were compared in terms of demographic properties such as age, parity, body mass index (BMI), hemoglobin value, neutrophil count, platelet count, neutrophil/ lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), mean platelet volume (MPV) and CRP. RESULTS: The groups were similar in terms of age, parity, BMI, hemoglobin and platelet count values (p>0.05). Neutrophil counts, CRP values, NLR and PLR were significantly higher and the MPV values were significantly lower in the study group (p<0.05). The parameter with highest sensitivity and specificity was NLR, which had similar diagnostic sensitivity and specificity as CRP. CONCLUSIONS: While the most commonly used laboratory tests for the diagnosis of PID are WBC, neutrophil and CRP, NLR should be considered as an even more sensitive marker. It was concluded that NLR could be used in addition to other CBC parameters for the diagnosis of PID.